The snake fight - Patton, Jack (Battle bugs, 2016)
"The Battle Bugs have discovered a tunnel that leads directly from Reptile Island to Bug Island. Max must plug it before the Battle Bugs' defenses fall! The tunnels connecting the islands hold more than either side bargained for--prehistoric creatures ready to battle! The fate of Bug Island rests on the sturdy shell of an ancient snail. Can one bug turn the tide of war?"--Back cover.